Plan estratégico para el mejoramiento del servicio del departamento de ventas del comercial CREVICREDITO, cantón Quevedo, periodo 2015-2019 - Rivadeneira Tenelema, Johanna Carolina (2016)
Globally, companies require the implementation of a strategic plan to strengthen the structures of work, and define objectives and strategies directed to fulfill his vision. Splitting the problem; How will provide a strategic plan for improving service sales department Commercial Crevicrédito? the design of a strategic plan for improving the service department sales Commercial Crevicrédito, Quevedo Canton, period 2015-2019, it will bring in business continuity by using strategies that help was raised as a general objective to strengthen the area sales and customer service; and establish contingency plans to counter external factors that negatively influence the marketing of their products. The methodology used was the application of interviews and surveys which determined the strategies contained in the plan: advertise, increasing vendors, advising clients and train human talent. Finally the projected budget of the Strategic Plan until 2019, which will give a new twist to the business by applying new strategies to compete in the market arises. With the approval of the Owner Manager. Keywords: Plan , Strategic Planning , Strategies